Computerized Study with 201T1 of the Cold Thyroid Node - Palermo, F.; Saitta, B.; Coghetto, F.; Tiberio, M.; Caldato, L. (Nuklearmedizin - NuclearMedicine, 1982)
Because of its physical and potassium-metabolic characteristics 201T1 is more suitable than 131Cs for radioisotopic studies of the cold thyroid nodule, with the further diagnostic possibility of quantitatively assessing intranodular behaviour for a specific differentiation among different kinds of neoformations. Using a gamma-camera on line with a computer data processing device, sequential scintiscans were recorded for the first 20-30 min after i. v. administration of 15-20 MCi\lkg of radiothallium; delayed sequences were taken at 40-60 min if intranodular uptake appeared. A quantitative appraisal was made of the differential 201Tl uptake-ratio between nodule and healthy thyroid tissue (density-index) and the multiparameter analysis of thyroid time/activity curves generated on the relative regions of interest (ROIs). This computerized study, in 120 out of 293 patients submitted to this radiothallium test, has shown a) diagnostic agreement between clinical-histological and radioisotopic findings in 76 out of 79 colloid-cystic or degenerative neoformations, in all 16 malignant and in 23 out of 25 hyperplastic benign nodules; b) significant statistical difference of the density-index in solid versus cystic but not between benign and malignant nodules; c) different 201T1 kinetics behaviour in different kinds of solid thyroid lesions with a satisfactory statistical difference of the radiothallium nodular dissapearance-index.